The role of human resources in anesthesia and intensive care units. - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Anesthesia and ICU teams consist of a variety of healthcare professionals, including anesthesiologists, critical care specialists, nurses, respiratory therapists, and support staff. The complexity of care delivered in these environments requires that each team member works in harmony, with roles clearly defined and communication channels open. As such, HRM in these structures focuses on recruitment, training, staff retention, and performance management.